Burden of Malaria in three Endemic Districts of Bhutan: Road to Malaria Elimination - Chhetri, Vishal; Dukpa, Tobgyel; Namgay, Rinzin; Wangchuk, Kesang; Pokrel, Hari Prasad (International Journal of Innovative Research in Medical Science, 2019)
Introduction: Bhutan is considered as a low endemic country for malaria. In the last decade, Bhutan has successfully reduced the number of malaria cases with the support from Global Fund and WHO. Sarpang, Samtse and Samdrup Jongkhar districts located in the Southern foothills of Bhutan records the most cases. Method: This retrospective study was undertaken with the available census record maintained in health centers of the three endemic districts and VDCP. Results: There were 892 confirmed malaria cases in 2009 and 41 cases in 2017 in three endemic districts. The slide positivity rate (SPR) declined from 2.2% in 2009 to 0.1% in 2017. The distribution of disease was significantly higher (p<0.05) amongst the male population with the increasing trend of Plasmodium vivax infection. The study found predominance of P. vivax in Samtse (93%), and Sarpang (62%) and Plasmodium falciparum in Samdrup Jongkhar (61%). The last four years (2014-2017) data showed that maximum cases detected were imported, followed by indigenous and introduced malaria; with 50%, 44% and 6%, respectively. The mortality and morbidity due to malaria has magnificently declined in the last decade. Conclusion: The large-scale implementation of vector control interventions, such as insecticide-treated bed nets, indoor residual spraying, free health care service and active vector surveillance has achieved a marked reduction in malaria incidence. Cross border malaria is still a huge challenge for elimination of malaria in Bhutan. Thus, imported malaria is an increasing problem due to high receptivity, and vulnerability.